Role of plant nutrients in enhancing productivity and managing diseases of oilseed Brassica (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard production and productivity commonly influenced not only the damage caused by biotic stresses but also by the nutrient supply for plant growth. Nutrient stress or surplus in plants causes them less vigorous and more susceptible to different diseases. High yields are normally obtained on deep fertile topsoil without a compact layer to facilitate root growth, and a porous crumb structure of the uppermost soil layer for rapid germination of the small seed of rapeseed-mustard. This is assisted by a neutral soil reaction and sufficient organic matter for optimal biological activity. The oilseed brassica crops damaged by several diseases, including Alternaria blight, white rust, downy mildew, Sclerotinia rot, and powdery mildew caused yield losses of 47%, 35%, 40% and 17%, respectively, which are of vital importance. The deficiency of nutrients has negative impact on plant health and yield level. In case of infection due to a disease, plants encounter the pathogen by producing inhibiting compounds although their production and transport is mainly dependent upon plant nutrients. Healthy plants are less susceptible to infections. Nutrient management of both micro and macronutrient is a challenging aspect for sustainable production in India because most of soils are nutrient deficient. The role of integrative plant nutrition is an important component in sustainable agriculture, because it is more cost effective and also environment friendly way to control plant disease. Adequate nutrients can achieve disease control to a certain level, but further control could be gained through cultural practices or conventional organic biocides that are eco-friendly. The advancements in averting such looses thus have lots of bearing on the growers, consumers and the society. The paper reviews the role of plant nutrient in managing the diseases and enhancing rapeseed-mustard production under Indian condition.